Recent and active tectonics in the western part of the Betic Cordillera - Ruiz-Constán, A.; Pedrera, A.; Galindo-Zaldivar, J.; Stich, D.; Morales, J. (Journal of Iberian Geology, 2012)
Based on new seismological and recent faulting data, we analyze five main sectors in the western part of the Betic Cordillera from an active tectonic perspective: i. The northwestern frontal sector of the cordillera, including the Morón de la Frontera area, with shallow (< 15 km depth) seismogenic active NE-SW reverse and strike-slip faults that do not reach the surface. ii. The Teba area, in the External Zones, which is deformed by sparse N-S to NW-SE normal faults with associated wedges of Quaternary sediments and active strike-slip faults at intermediate crustal levels. iii. The Ronda Basin, representing the major Late Miocene intramontane basin of the western Betic Cordillera, is mainly deformed by NNE-SSW and WNW-ESE folds and locally by NW-SE normal faults. iv. The internal part of the orogen, which is characterized by shallow (<40 km) and intermediate (40 to 120 km depth) seismicity beneath Málaga and the Alborán Sea, ENE-WSW folding, relief uplift, river incision and scarce active faults with surface expression. v. The Spanish Atlantic coast, which coincides with the western end of the Betic orogen, where Pliocene to Quaternary shallowmarine sedimentary rocks are deformed by meso-scale NW-SE oriented normal faults and few ENE-WSW reverse faults. These data support the recent tectonic activity of the western Betic Cordillera determined by the NW-SE Eurasian-African convergence with variable features from the mountain front, characterized by shallow deformations, up to the Internal Zones that mainly undergo uplift and intermediate seismicity.